2018
DOI: 10.1111/jog.13782
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal diseases and adverse pregnancy outcomes

Abstract: From last decade of the 20th century, numerous epidemiological studies and intervention trials have attempted to prove the relationships between maternal periodontal diseases and adverse pregnancy outcomes (APO). Periodontal diseases are considered a risk factor for APO, including preterm birth, fetal growth restriction, low birthweight, pre-eclampsia and gestational diabetes. However, the efficacy of periodontal treatment during pregnancy is controversial. Two pathogenic mechanisms might explain the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 62 publications
0
68
0
16
Order By: Relevance
“…The pulmonary, neurological complications and MODS was recorded in 16% of this group of women. [4][5][6] Among this group of women, the most often developing complication was hematological complications which was recorded in 33% of women and ophthalmological complications which was recorded in 33% of women. 7,8 It is significant to note that no renal and septic complications were seen in teenage women admitted for delivery with complication of preeclampsia and eclampsia.…”
Section: Teenage Mothersmentioning
confidence: 94%
“…The pulmonary, neurological complications and MODS was recorded in 16% of this group of women. [4][5][6] Among this group of women, the most often developing complication was hematological complications which was recorded in 33% of women and ophthalmological complications which was recorded in 33% of women. 7,8 It is significant to note that no renal and septic complications were seen in teenage women admitted for delivery with complication of preeclampsia and eclampsia.…”
Section: Teenage Mothersmentioning
confidence: 94%
“…Dentists in this survey had a limited understanding of oral health and its relation to pregnancy outcomes because (62.5%) of them believed that there was no association between periodontal diseases and adverse pregnancy outcomes. This result indicated that dentists in Jordan had not been updated with recent studies, which assured that periodontal diseases are risk factors for APO, including preterm birth, pre-eclampsia, low birth weight, and gestational diabetes (25). Several studies in the USA reported similar perceptions, where almost (40.0%) of dentists were uncertain about oralconditions and their effects on pregnancy (26)(27)(28).…”
Section: Knowledge Of Dentists About the Treatment Of Pregnant Womenmentioning
confidence: 99%
“…Szczególnie ważna może być zależność pomiędzy mikrobiotą jamy ustnej a nieprawidłowościami w przebiegu ciąży [39,40]. Od czasu gdy po raz pierwszy zaobserwowano zależność pomiędzy chorobami przyzębia a niską masą urodzeniową płodu, [41] liczne, choć nie wszystkie, badania epidemiologiczne wykazały związek pomiędzy chorobami przyzębia a przedwczesnym porodem, ograniczeniem wzrostu płodu, niską masą urodzeniową, stanem przedrzucawkowym oraz cukrzycą ciężarnych. Metaanalizy wskazują na istnienie nieznacznego związku pomiędzy paradontozą a przedwczesnym porodem oraz niską masą urodzeniową [42].…”
Section: Wpływ Mikrobioty Pochwy I Jamy Ustnej Na Mikrobiotę Macicy Iunclassified